Mercury contamination level and speciation inventory in Lakes Titicaca & Uru-Uru (Bolivia): Current status and future trends. (December 2017) - Guédron, S.; Point, D.; Acha, D.; Bouchet, S.; Baya, P.A.; Tessier, E.; Monperrus, M.; Molina, C.I.; Groleau, A.; Chauvaud, L.; Thebault, J.; Amice, E.; et al.
Abstract: Aquatic ecosystems of the Bolivian Altiplano (∼3800 m a.s.l.) are characterized by extreme hydro-climatic constrains (e.g., high UV-radiations and low oxygen) and are under the pressure of increasing anthropogenic activities, unregulated mining, agricultural and urban development. We report here a complete inventory of mercury (Hg) levels and speciation in the water column, atmosphere, sediment and key sentinel organisms (i.e., plankton, fish and birds) of two endorheic Lakes of the same watershed differing with respect to their size, eutrophication and contamination levels. Total Hg (THg) and monomethylmercury (MMHg) concentrations in filtered water and sediment of Lake Titicaca are in the lowest range of reported levels in other large lakes worldwide. Downstream, Hg levels are 3–10 times higher in the shallow eutrophic Lake Uru-Uru than in Lake Titicaca due to high Hg inputs from the surrounding mining region. High percentages of MMHg were found in the filtered and unfiltered water rising up from <1 to ∼50% THg from the oligo/hetero-trophic Lake Titicaca to the eutrophic Lake Uru-Uru. Such high %MMHg is explained by a high in situ MMHg production in relation to the sulfate rich substrate, the low oxygen levels of the water column, and the stabilization of MMHg due to abundant ligands present in these alkaline waters. Differences in MMHg concentrations in water and sediments compartments between Lake Titicaca and Uru-Uru were found to mirror the offset in MMHg levels that also exist in their respective food webs. This suggests that in situ MMHg baseline production is likely the main factor controlling MMHg levels in fish species consumed by the local population. Finally, the increase of anthropogenic pressure in Lake Titicaca may probably enhance eutrophication processes which favor MMHg production and thus accumulation in water and biota. Graphical abstract: Box plot presentation with error bars for percentage methylmercury over total mercury for filtered and unfiltered surface waters along the upstream - downstream gradient from Lake Titicaca to Uru-Uru. Vertical bar chart show the median (upper full line) and standard deviation (SD) of each data set (N is the number of samples). Highlights: A global inventory of Hg levels and species is done in Lake Titicaca hydrosystem. Lake Titicaca exhibits low Total Hg and MMHg concentrations in water and sediment. Lake Uru-Uru exhibits Hg levels 3 to 10 times higher than in Lake Titicaca. Percentages of MMHg are high in all waters rising up from <1 to ∼50% of THg. Enhanced i n situ MMHg production by eutrophication controls Hg levels in fish. Abstract : High in situ MMHg production and accumulation in Lake Titicaca hydrosystem can be enhanced by local eutrophication and controls MMHg levels in fish species.